7.2: A Novel FOD Solution with High‐PPI Flexible Sensor under OLED Panel. (26th August 2021) - Lu, Feng; Lian, Lu; Yu, Haochi; Li, Kai; Zhang, Bo; Yao, Qijun; Zeng, Yang; Wu, Yaodong; Ding, Yuan
Abstract : A novel FOD solution is presented in this paper. TFT‐based flexible photo sensors of 725 PPI and 1016 PPI were developed and characterized. Adapted to the OLED panel with integrated pinhole imaging system, the feasibility of large area FOD function was confirmed.